PENGARUH PERSEPSI DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MEMILIH KARIR KONSULTAN PAJAK - Dewi Kususma Wardani,; Ratih Novianti, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to examine the effect of labor market perceptions and considerations on the interest in choosing a tax consultant career. The independent variable in this study is the perception and consideration of the labor market, while the dependent variable is the interest in choosing a tax consultant career. The sample in this study were students of the Department of Accounting, Universitas Sarjanawiyata Tamansiswa Yogyakarta. The sampling technique used the snowball sampling method, data was collected by distributing questionnaires through social media. The analytical method used is multiple linear regression analysis with IBM SPSS Statistics 20. Based on the results of the analysis, it is shown that perception has no effect on interest in choosing a tax consultant career and labor market considerations have no effect on interest in choosing a tax consultant career